Reconstructing Islamic Criminal Liability for Economic Crimes: A Maqasid-Based Framework for Indonesia’s Sharia Finance - Imroatul Azizah; Mabarroh Azizah; Saiful Bakhri; Suqiyah Musafa'ah; Amang Fathurrohman; Shofa Robbani (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2026)
The rapid expansion of Islamic finance in Indonesia has generated significant legal ambiguity in distinguishing civil contractual breaches from criminal economic misconduct under Sharia-compliant transactions. This ambiguity weakens legal certainty, complicates judicial enforcement, and challenges judges, regulators, and Sharia supervisory institutions in addressing increasingly complex financial misconduct involving corporate structures, digital finance, and systemic fraud. The particular study aimed to reconstruct Islamic criminal liability for economic crimes through a maqāṣid-based framework applicable to Indonesia’s contemporary Sharia finance system. Employing a normative-interpretive approach, the study integrated philosophical-normative, comparative, and functionalist-pragmatic analyses of classical fiqh jinayah, uṣul fiqh, KHES, DSN-MUI fatwas, and contemporary legal scholarship on economic crime and corporate liability. The findings revealed that the distinction between civil and criminal liability fundamentally depends on two interrelated criteria, namely intentional corruption (qaṣd ifsad) and systemic or compound harm (darar ‘amm/murakkab). Based on these findings, the study formulated the “Three-Pillar Framework” and the “Tiered Maqasidi Model” as systematic mechanisms for determining criminal liability in contemporary Islamic economic activities. The study contributed to the development of fiqh jinayah and maqāṣid syarī‘ah by extending Islamic criminal liability to corporate, participatory, and systemic economic crimes while providing an operational framework for judges, regulators, and Sharia supervisory institutions. Accordingly, the proposed framework offered a systematic foundation for distinguishing civil liability from criminal responsibility in contemporary Islamic finance.